Nationwide Non-Communicable Disease Risk Factors Profile in Bangladesh. (June 2015) - Jesmin, Subrina; Rahman, Md Arifur; Habib, AKM Ahsan; Islam, Md Majedul; Sultana, Sayeeda Nusrat; Zaedi, Sohel; Khatun, Tanzila; Sohael, Farzana; Yamaguchi, Naoto; Okazaki, Osamu; Iwashima, Yoshio; Kawano, Satoru
Abstract : Background: In 2007, non-communicable diseases (NCDs) were reported to represent the highest cause-specific mortality burden among adults in Bangladesh. To date, a comprehensive nationally representative data are lacking on the NCDs using the full protocol of WHO-STEP approach to describe the NCDs risk factors in Bangladesh. The objectives of this study were to describe the prevalence of selected NCD risk factors in Bangladesh through a nationwide analysis. Method: Total 22454 Bangladeshi population more than 15 years old were included in this analysis. The sampling design was multistage stratified clustering including seven divisions of Bangladesh in both rural and urban areas. The target population for this survey includes all men and women aged 15 years or older who consider Bangladesh to be their primary place of residence excluding those who were in military base or group quarters (e.g. a dormitory) and who were institutionalized. Result: Of the study participants that took part in the survey, about 45.9% were males and 54. 1% were females, 52.78% were from rural areas, 47.22% were from urban areas and about one in four (24.4%) had no formal education. Blood pressure, fasting blood sugar and lipid profiles were measured in 99%, 85% and 60% respectively of the 20, 039 participants. In Bangladeshi population the total prevalence of selected risk factors are as follows: smoking (21.7%), smokeless tobacco (30.8%), low intake of fruits and vegetables per day (86.9%), inadequate physical activity (41.4%), alcohol consumption (0.7%), raised blood pressure (23.8%), diabetes (10.6%), overweight and obesity (24.1%), abdominal obesity (19.7%), raised total cholesterol (28.0%), hypertriglyceridemia (33.8%), low HDL level (65.7%). Nearly half of the participants use any types of tobacco, 17.8% reported having been diagnosed with high blood pressure, and 6.5% reported having diabetes. Overweight, abdominal obesity, physical inactivity, low intake of fruits and vegetables per day, smokeless tobacco, raised cholesterol and raised blood pressure (BP)were more common in females than males, 25.5% vs 22.7%, 31.1 vs 8.3, 60.1% vs 22.6%, 93.1% vs 80.6%, 31.9 vs 29.6, 30.7% vs 25.3% and 26.6%vs 21.0%. A total of 5.07% of the teenagers had one risk behaviour, 20.74% had two, 28.57% had three, and 43.37% presented all the investigated risk behaviors. Only 2.25% did not display any of the analysed risk behaviours. Conclusion: Diabetes, high blood pressure, high TG, low HDL, and obesity are a public health concerns in Bangladesh. Adequate and continuous monitoring of NCD risk factors in Bangladesh is needed, and the surveillance findings should be used in health promotion and disease prevention activities.